Isolation, Screening And Identification Of Protease Producing Fungi From Rhizosphere Soil And Optimisation Of Ph, Incubation Time And Inducer Concentration For Enhanced Protease Production - V.MOHANASRINIVASAN; VANI SHANKAR; RAISHA ELIZABETH; SOUMYA A.R; C.SUBATHRA DEVI (International Journal of Pharma and Bio Sciences, 2012)
Protease is any enzyme that conducts proteolysis and accounts for about 60% of the total enzyme market. These enzymes find applications in waste treatment, bioremediation process, in detergents and in leather industry. In the present research work protease producing microorganisms were isolated from soil samples collected from rhizosphere and non-rhizosphere region by spread plate technique. The isolated organisms were screened for their protease producing abilities. The strain that gave positive result in screening was identified as Aspergillus niger by analyzing the colony morphology and using LCB staining test. The important production parameters like pH, inducer concentration and incubation time were optimized. Maximum enzyme activity of 307.5 µmol/ml-min was observed at pH 9, 0.05% inducer concentration and after 96 hours of incubation.